2019
DOI: 10.1021/acs.jmedchem.8b02004
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Early Clinical Development of an Inhibitor of 5-Lipoxygenase Activating Protein (AZD5718) for Treatment of Coronary Artery Disease

Abstract: 5-Lipoxygenase activating protein (FLAP) inhibitors attenuate 5-lipoxygenase pathway activity and reduce the production of proinflammatory and vasoactive leukotrienes. As such, they are hypothesized to have therapeutic benefit for the treatment of diseases that involve chronic inflammation including coronary artery disease. Herein, we disclose the medicinal chemistry discovery and the early clinical development of the FLAP inhibitor AZD5718 (12). Multiparameter optimization included securing adequate potency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Pettersen et al report the discovery and optimization of a series of novel inhibitors of 5-lipooxygenase-activating protein, which stimulates the production of leukotrienes, important mediators in the pathogenesis and progression of atherosclerosis [2]. In particular, compound AZD5718, (1 R ,2 R )-2-{4-[3-methyl-1-(tetrahydro-2 H -pyran-2-yl)-1 H -pyrazol-5-yl]benzoyl}- N -(4-oxo-4,5,6,7-tetrahydropyrazolo-[1,5- a ]pyrazin-3-yl)cyclohexanecarboxamide, demonstrated a favorable pharmacokinetic and safety profile in rats and dogs [3]. This led to phase-I studies in healthy subjects, which showed a strong relationship between plasma concentrations of AZD5718 and inhibition of both leukotriene B4, involved in inflammation, and leukotriene E4, a cysteinyl leukotriene also involved in inflammation [3].…”
Section: Inhibition Of 5-lipoxygenase-activating Protein: a New Thmentioning
confidence: 99%
“…Pettersen et al report the discovery and optimization of a series of novel inhibitors of 5-lipooxygenase-activating protein, which stimulates the production of leukotrienes, important mediators in the pathogenesis and progression of atherosclerosis [2]. In particular, compound AZD5718, (1 R ,2 R )-2-{4-[3-methyl-1-(tetrahydro-2 H -pyran-2-yl)-1 H -pyrazol-5-yl]benzoyl}- N -(4-oxo-4,5,6,7-tetrahydropyrazolo-[1,5- a ]pyrazin-3-yl)cyclohexanecarboxamide, demonstrated a favorable pharmacokinetic and safety profile in rats and dogs [3]. This led to phase-I studies in healthy subjects, which showed a strong relationship between plasma concentrations of AZD5718 and inhibition of both leukotriene B4, involved in inflammation, and leukotriene E4, a cysteinyl leukotriene also involved in inflammation [3].…”
Section: Inhibition Of 5-lipoxygenase-activating Protein: a New Thmentioning
confidence: 99%
“…Structure of AZD5718 ((1 R ,2 R )‐2‐{4‐[3‐Methyl‐1‐(tetrahydro‐2 H ‐pyran‐2‐yl)‐1 H ‐pyrazol‐5‐yl]benzoyl}‐N‐(4‐oxo‐4,5,6,7‐tetrahydropyrazolo[1,5‐ a ]pyrazin‐3‐yl)cyclohexanecarboxamide) …”
mentioning
confidence: 99%
“…In vitro studies indicate that cytochrome P450 (CYP) 3A4 and CYP3A5 are involved in the metabolism of AZD5718, with glucuronidation by uridine 5’‐diphosphate glucuronosyltransferases 1A1, 1A3, and 1A4 also contributing to metabolism . AZD5718 does not inhibit CYP isoforms 1A2, 2C8, 2C9, 2C19, 2D6, or 3A4 (IC 50 > 20 µM) or P‐glycoprotein (IC 50 > 100 µmol/L).…”
mentioning
confidence: 99%
See 2 more Smart Citations